2011
DOI: 10.4028/www.scientific.net/amr.233-235.1388
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Tamarind-Seed Thickener for Pigment Printing on Cotton

Abstract: This research studied the potential and efficiency of tamarind kernel powder as a thickener for pigment printing on cotton fabric in comparison with the commercial synthetic thickener. Two kinds of tamarind seed were studied. Both of tamarind seeds contained about 30% based on dry weight of outer seed coating and 70% of dry weight of tamarind kernel powder. The approximate composition of tamarind kernel powder were 2.39 – 3.19% fat, 16.43 – 17.07% protein, 1.20 – 1.68% crude fiber and 3.42-3.74% moisture based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Microwave irradiation using only hot water allows milder reaction conditions, which offer lower production costs, minimization of wastes when compared with the use of alkalis, and maintains the physicochemical characteristics of crude polysaccharides. It has been reported for a variety of matrices including corn pericarp, wheat bran, flax shives, tamarind kernel, mulberry leaves, brewers' spent grain, watermelon rinds, tea flower, mushrooms, or traditional Chinese medicinal plants . The control of MWE extraction conditions is important to limit hydrolytic cleavage of polysaccharide chains or alter the compositions that would enrich in some monomers .…”
Section: Applications Of Microwave Assisted Water Extractionmentioning
confidence: 99%
“…Microwave irradiation using only hot water allows milder reaction conditions, which offer lower production costs, minimization of wastes when compared with the use of alkalis, and maintains the physicochemical characteristics of crude polysaccharides. It has been reported for a variety of matrices including corn pericarp, wheat bran, flax shives, tamarind kernel, mulberry leaves, brewers' spent grain, watermelon rinds, tea flower, mushrooms, or traditional Chinese medicinal plants . The control of MWE extraction conditions is important to limit hydrolytic cleavage of polysaccharide chains or alter the compositions that would enrich in some monomers .…”
Section: Applications Of Microwave Assisted Water Extractionmentioning
confidence: 99%
“…From our previous work, it was found that these two types of tamarind seed had a slightly different extent of the husk and the kernel components [8]. The dye powder which was to be used for dyeing the cotton and silk fabrics, was the soluble part accounting for about 55% by weight of both tamarind seed husks.…”
Section: A Composition Of the Tamarind Seedsmentioning
confidence: 99%
“…In our previous work [8], the extracted tamarind kernel which composes mainly of the hetero-polysaccharide compound, xyloglucan, was studied to use as a thickener for pigment printing on cotton fabric. The results found that the prepared tamarind gum had desired thickening properties for textile printing, providing color yield and rubbing fastness of the print comparable to those of the commercial synthetic thickener printing.…”
mentioning
confidence: 99%
“…Its molecular weight ranges from 720 to 880 kDa (Freitas et al, 2005). Xyloglucan contains the major soluble sugars such as pentose (20%), mannose (17%-35%), and glucose (11%-80%) (Tepparin et al, 2011). When dissolved in water, it forms a viscous solution (Sumathi & Ray, 2002) and is utilized as an emulsifier, fiber, and rheology modifier in various applications (Gupta et al, 2010).…”
Section: Tamarind Seed Xyloglucan (Gum)mentioning
confidence: 99%